Optimization P-nitrotoluene Removal Efficiency in Aqueous Solution by Photocatalyticozonation Reaction - Ahmed, Lina Shaheed; Mazaheri, Hossein; Hassani, Ali (Journal of Petroleum Research and Studies, 2025)
p-Nitrotoluene (PNT) is a hazardous material suspected of causing hormone disruption. Its degradation in aqueous solutions was studied using photochemical ozonation with ZnO as a catalyst and UV radiation. Various factors, including PNT concentration, ZnO concentration, pH, ozone flow rate, and UV exposure time, were varied in laboratory experiments. Response surface methodology (SRM) and central composite rotatable design (CCRD) were used to optimize the process. The PNT removal efficiency ranged from 47% to 99.5%, with a high correlation (R² = 0.9558). Significant factors included UV exposure time, pH, ozone flow rate, ZnO concentration, and initial PNT concentration. The maximum removal efficiency was achieved with 76.701 ppm of initial PNT, 0.16 g/l ZnO, pH 8.235, 3.516 ozone flow rate, and 99.548 minutes of UV exposure.